Vuokatti Sports Institute - Ski tunnel (2011)
The Vuokatti ski tunnel is a legend - it began as a crazy idea, which then became an international success story. It has been said that when the first news broke out about the Vuokatti ski tunnel, many were convinced that the idea of a year-round underground ski-trail had to be crazy. However, the success of this ski tunnel as a training and testing place speaks for itself. The skiing properties of the tunnel located adjacent to Vuokatti Sports Institute are in a class of their own. Controlled skiing conditions enable year-round practising. Consequently it's no wonder that Vuokatti is a venue where internationally renown ski-jumpers and cross-country specialists as well as Finnish biathlon champions can be encountered even in the middle of the summer.